2016 IEEE 21st International Conference on Emerging Technologies and Factory Automation (ETFA) 2016
DOI: 10.1109/etfa.2016.7733572
|View full text |Cite
|
Sign up to set email alerts
|

Automated Decision Support IoT Framework

Abstract: During the past few years, with the fast development and proliferation of the Internet of Things (IoT), many application areas have started to exploit this new computing paradigm. The number of active computing devices has been growing at a rapid pace in IoT environments around the world. Consequently, a mechanism to deal with this different devices has become necessary. Middleware systems solutions for IoT have been developed in both research and industrial environments to supply this need. However, decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several mathematical aspects of IoT devices signals processing are presented in [20,21]. The incorporation of IoT manages to improve efficiency in energy consumption we can see in the [3,6,7,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several mathematical aspects of IoT devices signals processing are presented in [20,21]. The incorporation of IoT manages to improve efficiency in energy consumption we can see in the [3,6,7,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed inventory management system was simulated with inventory management scenarios using IoT technology. Lunardi et al [8] presented a decision support IoT framework with existing rule-based decision management systems (i.e., COMPaaS [39] and COBASEN [40]); the framework was used to support the discovery and selection of IoT devices for IoT applications. This paper does not directly mention self-adaptation.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In this context, self-adaptive software can be applied to dynamic IoT environments because it alters its behavior or structure in dynamic environments at runtime [5,6]. In addition, there have been several studies on the application of self-adaptive software in various IoT environments such as inventory management systems [7], smart rooms [8], healthcare [9,10], middleware [11], emergency handling systems [12], smart city [13,14], and IoT networks [15,16,17]. However, each study has its own aspects, distinct characteristics, and target domains.…”
Section: Introductionmentioning
confidence: 99%
“…Lunardi, Amaral, Marczak, Hessel, and Voos [16] presented a decision support IoT framework. By analyzing others IoT middleware systems and frameworks the researchers found that they do not provide methods to allow automated decision making based on device data stream.…”
Section: Related Workmentioning
confidence: 99%